Examining the effects of HIV self-testing compared to standard HIV testing services in the general population: A systematic review and meta-analysis. (August 2021) - Jamil, Muhammad S.; Eshun-Wilson, Ingrid; Witzel, T. Charles; Siegfried, Nandi; Figueroa, Carmen; Chitembo, Lastone; Msimanga-Radebe, Busisiwe; Pasha, Muhammad S.; Hatzold, Karin; Corbett, Elizabeth; Barr-DiChiara, Magdalena; Rodger, Alison J.; et al.
Abstract: Background: We updated a 2017 systematic review and compared the effects of HIV self-testing (HIVST) to standard HIV testing services to understand effective service delivery models among the general population. Methods: We included randomized controlled trials (RCTs) comparing testing outcomes with HIVST to standard testing in the general population and published between January 1, 2006 and June 4, 2019. Random effects meta-analysis was conducted and pooled risk ratios (RRs) were reported. The certainty of evidence was determined using the GRADE methodology. Findings: We identified 14 eligible RCTs, 13 of which were conducted in sub-Saharan Africa. Support provided to self-testers ranged from no/basic support to one-on-one in-person support. HIVST increased testing uptake overall (RR:2.09; 95% confidence interval: 1.69–2.58; p < 0.0001;13 RCTs; moderate certainty evidence) and by service delivery model including facility-based distribution, HIVST use at facilities, secondary distribution to partners, and community-based distribution. The number of persons diagnosed HIV-positive among those tested (RR:0.81, 0.45–1.47; p = 0.50; 8 RCTs; moderate certainty evidence) and number linked to HIV care/treatment among those diagnosed (RR:0.95, 0.79–1.13; p = 0.52; 6 RCTs; moderate certainty evidence) were similar between HIVST and standard testing. Reported harms/adverse events with HIVST were rare and appeared similar to standard testing (RR:2.52: 0.52–12.13; p = 0.25; 4 RCTs; very low certainty evidence). Interpretation: HIVST appears to be safe and effective among the general population in sub-Saharan Africa with a range of delivery models. It identified and linked additional people with HIV to care. These findings support the wider availability of HIVST to reach those who may not otherwise access testing. Funding: This review was funded by the Bill and Melinda Gates Foundation (OPP1177903), Unitaid (PO#101400-600 and PO#84770-600) and the United States Agency for International Development (US-2015-0839 and US-2016-940). TCW, AJR, PW received grants during the conduct of the study (National Institute for Health Research Programme Grants for Applied Research Programme [PG-482 1212-20006]). EC (London School of Hygiene & Tropical Medicine), EG (ViiV Healthcare research grant) and CJ (the Bill and Melinda Gates Foundation, Unitaid, and the United States Agency for International Development) received grants outside of submitted work.